Prevalence of Five BRCA1/2 Mutations in Bulgarian Breast Cancer Patients - Katia Kovacheva; Zornitsa Kamburova; Savelina Popovska; Dobromir Dimitrov; Ivan Ivanov; Maria Simeonova (Journal of Biomedical & Clinical Research)
Detection of mutations in breast cancer 1 (BRCA1) and breast cancer 2 (BRCA2) gene is an effective method of early diagnosis and prevention of breast cancer (BC). The mutational spectrum of both genes in Bulgarian population has not been studied in depth. The aim of this study was to investigate the prevalence of five deleterious BRCA1/2 point mutations in high-risk BC women, selected according to the National Comprehensive Cancer Network (NCCN) Guidelines including early age of onset, triple-negative BC and family history of breast or ovarian cancer. The prevalence of two BRCA1 mutations (C61G and 5382insC) and three BRCA2 mutations (6079del4, 9326insA and 9908delA) was evaluated in 80 females with BC, obtained from the Cancer Registry of University Hospital - Pleven. Genetic testing was performed by direct DNA sequencing. One deleterious mutation (5382insC in exon20 in BRCA1) was been found in two patients (2.5%). Both women were diagnosed with BC before age 45. The prevalence of BRCA mutations established in our study was lower than the one found in another preliminary study on Bulgarian population. We concluded that this discrepancy was due to the genetic heterogeneity of the population and the specific mutational spectrum of the BC patients from the Pleven region.